Assessment of European Integration in Conditions of Globalization - Konstantinos Chainas (Research Developments in Arts and Social Studies Vol. 1, 2022)
In this paper we investigate the subject of European integration, with regard to the problems resulting from the terrorist attacks by fanatic Islamists, and, more generally, the impact of the migrant/refugee problem. Prompted by the latest global financial meltdown, which also touched the Eurozone critical voices against the E.U. project, and predominantly the Euro and the Eurozone, have been raised. We will examine the risks of the E.U. project’s failure, as well as the opportunities of economic and political integration for Europe. We will also look into the impact of the proposals put forward by various analysts advocating the disintegration of the Eurozone, or in favour of the introduction of a Northern and Southern Euro. Is ‘Brexit’ proof of the failure of the project for the E.U.’s integration, or can it ultimately trigger an acceleration of European integration? Answers to this, as well as other questions pertaining to this issue, are sought in the course of the present paper. According to our analysis, the leaders of the E.U. and European societies have two options: the first one, which is more in favour, owing to the present context as well as the forces of stagnation, is a setback in the procedure of furthering European integration, with the simultaneous cancellation of the project for Europe’s democratic integration in the medium to long term.; the other option is the strengthening of European integration, with the rapid transformation of the monetary union into a new political and economic union, of the Federation type, which will constitute the most convincing and all-round response on the part of European societies to Euro-skepticism, anti-Europeanism and all forms of nationalism, seeking to dissolve, in one way or another, the Eurozone, and ultimately the E.U. The greater good of all countries, rich and poor, Northern and Southern, Eastern and Western, requires a single, democratic, European political plan: the building of our future common European home – the United States of Europe.